Characterization of bacteriocins produced by Lactobacillus species against adhesion and invasion of Listeria monocytogenes isolated from different samples. (January 2022) - Golmoradi Zadeh, Rezvan; Asgharzadeh, Sajjad; Darbandi, Atieh; Aliramezani, Amir; Masjedian Jazi, Faramarz
Abstract: Background: Listeria monocytogenes is an important difficult to control and eradicate foodborne pathogen due to its resistance properties to extreme conditions. Bacteriocins produced by lactic acid bacteria (LAB) can be considered as natural alternatives for safety and quality of foods, since these molecules offer antimicrobial activity against other bacteria. Methods: In this study, Lacticaseibacillus casei, Lactiplantibacillus plantarum, and L. monocytogenes isolates were first characterized by phenotypical tests and 16S rRNA gene using PCR. Then, six types of bacteriocins produced by Lactobacilli strains were identified using molecular tests. The ability of these strains to compete with L. monocytogenes for adhesion and invasion to HT-29 cells was evaluated through colony count and MTT assay. Finally, the level of bacteriocins expression was assessed using qRT-PCR. Results: L. monocytogenes strains were categorized from A1 to A8 based on the source of isolation. In the adhesion assay, L. casei + L. monocytogenes isolated from milk and Lpb plantarum + L. monocytogenes isolated from feces presented the maximum adherence values. Further, Lpb plantarum + L. monocytogenes isolated from blood invaded to HT-29 cell line at the highest level. Eventually, L. casei + Lpb plantarum + L. monocytogenes isolated from placenta revealed more expression levels in comparison with other groups. Conclusion: These results suggest a practical approach to classifying bacteriocins into functional groups that could be used for identifying the best mixture of bacteriocins for usage against L. monocytogenes .